The Boys. Season 3 [videorecording (DVD)] - Kripke, Eric (Sony Pictures Home Entertainment, 2023)
It's been a year of calm. Homelander (Antony Starr) has been subdued. Butcher (Karl Urban) works for the government, supervised by Hughie (Jack Quaid), but both men itch to turn this peace and quiet into blood and bone. So when the Boys learn of a mysterious anti-supe weapon, it sends them crashing into the Seven, starting a war, and chasing the legend of the first superhero: Soldier Boy (Jensen Ackles).